Health Benefit of Coconut Milk - Suyitno T. (Indonesian Association of Food Technologists, 2003)
Indonesia, India and the Philippines are the major world coconut producers. Of the three leading producers, the Philippines is the biggest supplier to world trade in the form of coconut oil. Indonesia and India use the bulk of their coconut internally, both as food nuts and as coconut oil. The main use of coconut in Indonesia is for coconut milk. Indonesians are reported as moderate coconut milk consumers, with a per capita consumption of 6.5-8.2 kilograms. Coconut milk is an important part of the dietary in coconut producing countries like Indonesia. It is valued mainly for its characteristic nuttyflavor and for its nutritional content. Coconut milk is used as an ingredient in many fish, shellfish, meat, poultry, vegetable dishes, yellow rice, delicious rice (nasi gurih), confectionaries, and baked goods. The main component of coconut milk is coconut oil, it account for 38% by weight. Coconut oil is naturally saturated, about 92% consists of saturated fatty acids., mainly are medium chain fatty acids (MCFA). About 50 % offatty acid in coconut oil is lauric (CI), for this reason, it is called the